Nonexistence of nonzero derivations on some classes of zero-symmetric 3-prime near-rings - Ahmed A. M. Kamal; Khalid H. Al-Shaalan (Український математичний журнал, 2014)
We give some classes of zero-symmetric 3-prime near-rings such that every member of these classes has no nonzero derivation. Moreover, we extend the concept of “3-prime” to subsets of near-rings and use it to generalize Theorem 1.1 due to Fong, Ke, and Wang concerning the transformation near-rings M o (G) by using a different technique and a simpler proof. Наведено дєякі класи 3-простих майже-кілець з нульовою симєтрією таких, що будь-який елемент цих класів не має ненульової похідної. Крім того, поняття „3-простих" узагальнено на підмножини майже-кілець i застосовано, щоб узагальнити теорему 1.1 Фонга, Ке i Ванга про трансформацію майже-кілець M o (G) за допомогою іншої техніки та більш простого доведення.